Epidemiology of Invasive Haemophilus influenzae Serotype a Disease—United States, 2008–2017. (26th June 2020) - Soeters, Heidi M; Oliver, Sara E; Plumb, Ian D; Blain, Amy E; Zulz, Tammy; Simons, Brenna C; Barnes, Meghan; Farley, Monica M; Harrison, Lee H; Lynfield, Ruth; Massay, Stephanie; McLaughlin, Joseph; et al.
Abstract: Background: Haemophilus influenzae serotype a (Hia) can cause invasive disease similar to serotype b; no Hia vaccine is available. We describe the epidemiology of invasive Hia disease in the United States overall and specifically in Alaska during 2008–2017. Methods: Active population- and laboratory-based surveillance for invasive Hia disease was conducted through Active Bacterial Core surveillance sites and from Alaska statewide invasive bacterial disease surveillance. Sterile-site isolates were serotyped via slide agglutination or real-time polymerase chain reaction. Incidences in cases per 100 000 were calculated. Results: From 2008 to 2017, an estimated average of 306 invasive Hia disease cases occurred annually in the United States (estimated annual incidence: 0.10); incidence increased by an average of 11.1% annually. Overall, 42.7% of cases were in children aged <5 years (incidence: 0.64), with highest incidence among children aged <1 year (1.60). Case fatality was 7.8% overall and was highest among adults aged ≥65 years (15.1%). Among children aged <5 years, the incidence was 17 times higher among American Indian and Alaska Native (AI/AN) children (8.29) than among children of all other races combined (0.49). In Alaska, incidences among all ages (0.68) and among children aged <1 year (24.73) were nearly 6 and 14 times higher, respectively, than corresponding US incidences. Case fatality in Alaska was 10.2%, and the vast majority (93.9%) of cases occurred among AI/AN. Conclusions: Incidence of invasive Hia disease has increased since 2008, with the highest burden among AI/AN children. These data can inform prevention strategies, including Hia vaccine development. Abstract : Invasive Haemophilus influenzae serotype a disease has increased, with the highest incidence among American Indian and Alaska Native children.